ANALISIS BIAYA TRANSAKSI USAHA BUDIDAYA UDANG VANAME DI KECAMATAN KETAPANG, KABUPATEN LAMPUNG SELATAN - Fitri, Annisa; Saty, Fadila Marga; Luhur, Estu Sri; Rachman, Muhamad Emil (Universitas Galuh, 2023)
Vaname shrimp is a commodity that has high economic value so that it is widely cultivated by Indonesian people. Apart from the production costs incurred, there are also transaction costs that are often not taken into account by cultivators. The purpose of this study was to identify components and calculate transaction costs and analyze the economic efficiency of vannamei shrimp farming in Ketapang District based on transaction costs incurred. This study uses secondary and primary data with samples selected by cluster proportional simple random sampling. The selected respondents were vannamei shrimp cultivators from six vannamei shrimp pond center villages with traditional, semi-intensive and intensive technology as many as 30 people. The data analysis method used is descriptive quantitative and qualitative. The data obtained is then analyzed by transaction cost analysis. The results showed that the components of the transaction costs of the vannamei shrimp farming business and their ratios consisted of market information costs (0.02), input and output costs (0.01), implementation costs (0.19), licensing fees (0.23) , and levy fees (0.55). The economic efficiency of aquaculture can be seen from the ratio of transaction costs to production costs and revenues of 0.08 and 0.04 respectively.